Determination of the quantity and topography dynamics of the LCA+-dendritic cells in rat thymus in early postnatal period in norm and after the prenatal administration of the dexamethasone - M. A. Voloshyn; Ye. O. Aravitskiy; O. G. Kushch (Zaporozhye State Medical University, 2017)
Purpose was to study the dynamics of LCA+-dendritic thymus cells in newborn rats in the postnatal period after administration of dexamethasone in the intrauterine period. Materials and methods. The study was performed on 144 white nonlinear rats on the 1st-3rd, 5th, 9th, 14th, 21st, 30th days after birth. There are 3 groups with 48 rats in each group: 1 - intact group; 2 - experimental group of rats, who received peritoneal injection of 0.05 ml of dexamethasone (in dilution 1:40) on the 18th day of the prenatal period, and a control group of rats receiving 0.05 ml of 0.9 % NaCl according to M. A. Voloshyn. To study the dynamics of dendritic cells in the thymus carrying the α-D mannose receptors, LCA-lectin was used. Results. It has been established that the maximum content of LCA+-dendritic thymus cells in the intact (3.92 ± 0.65), experimental (3.41 ± 0.49) and control (4.07 ± 0.53) groups occurs on the 1st day after birth. The minimum number of LCA+-dendritic cells was detected on the 5th day in the intact (1.88 ± 0.37) and control (1.73 ± 0.34) groups, and their minimum in the experimental group (2.35 ± 0.48) was determined on the 30th day after birth. In the experimental group from the 5th day to the 9th day a significantly higher number of LCA+-dendritic cells than in the comparison groups was detected. Conclusions. The introduction of dexamethasone in the prenatal period leads to the significant increase in the LCA+-dendritic cell content in the experimental group from the 5th to the 9th day of life, which indirectly coincides with the increase in the number of peripheral and mitotic dividing lymphocytes in the thymus of rats in the postnatal period.